2009
DOI: 10.1111/j.1750-3841.2009.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Super Chilling Enhances Preservation of the Freshness of Salted Egg Yolk During Long‐Term Storage

Abstract: Pasteurized egg yolk with 10% (w/w) salt was stored at 5, -5, -15, -20, and -30 degrees C for 1 to 6 mo, respectively. Changes in generation of volatiles of the stored samples (5 and -5 degrees C for 6 mo) were analyzed by SPME-GC-MS. Emulsifying properties of egg yolk stored at -5, -15, -20, and -30 degrees C for 1 mo, respectively, were also evaluated by measurement of emulsion particle diameters in model emulsions prepared with the yolk samples. In addition, structural changes in low-density lipoprotein (LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…1,2) These phenomena should be suppressed to maintain the quality of the food emulsion. Many factors associated with destabilization of O/W emulsions during freezing have been suggested: (1) Denaturation of the emulsifier and stabilizer because of low-temperature preservation, 3,4) (2) change in the amount of emulsifier absorbed or its conformation at the interface, 1,5) (3) increase in internal stress caused by volumetric expansion of water into ice, 5,6) (4) aggregation of oil droplets due to freeze concentration, 5,7) and (5) partial coalescence of oil droplets by bridge-building among fat crystals. 8,9) It has been experimentally determined that crystallization of oil is likely the main cause of the destabilization of O/ W emulsions, 1,11) and oil-rich O/W emulsions are commonly less stable toward freezing.…”
mentioning
confidence: 99%
“…1,2) These phenomena should be suppressed to maintain the quality of the food emulsion. Many factors associated with destabilization of O/W emulsions during freezing have been suggested: (1) Denaturation of the emulsifier and stabilizer because of low-temperature preservation, 3,4) (2) change in the amount of emulsifier absorbed or its conformation at the interface, 1,5) (3) increase in internal stress caused by volumetric expansion of water into ice, 5,6) (4) aggregation of oil droplets due to freeze concentration, 5,7) and (5) partial coalescence of oil droplets by bridge-building among fat crystals. 8,9) It has been experimentally determined that crystallization of oil is likely the main cause of the destabilization of O/ W emulsions, 1,11) and oil-rich O/W emulsions are commonly less stable toward freezing.…”
mentioning
confidence: 99%
“…Hexanal, which has been reported in scrambled eggs, has been identified as a product of lipid oxidation (Matiella and Hsieh 1991), and was one of the major volatile compounds in cooked yolk (Warren and others 1995). In addition, it was shown that hexanal increased in salted egg yolk stored at 5 °C (Yanagisawa and others 2009). Boyd and others (1992) suggested that hexanal was formed by the degradation of linoleic acid.…”
Section: Resultsmentioning
confidence: 99%
“…In recent research, it was reported that super chilling is an effective means for preserving salted egg yolk during long‐term storage (Yanagisawa and others 2009), indicating that super chilling (−5 °C) is more adequate than storage at other temperatures (5 °C, −15 °C, −20 °C, and −30 °C) for suppressing the generation of volatiles, structural changes in lipoprotein, and reducing the emulsifying properties of salted egg yolk. Shell eggs freeze at −5 °C during long‐term storage but do not freeze at 0 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The volatile compounds of LWE samples were extracted using headspace solid-phase microextraction (HS-SPME) and analyzed by gas chromatography-mass spectrometry (GC-MS), as previously reported [ 23 ], with minor modifications. In brief, a 2.0 g of LWE in a 15 mL glass vial were added 0.60 g of sodium chloride and 50 µL of the internal standard and immediately sealed with a screw cap with a silicone septum; then, the samples were equilibrated for 15 min at 45 °C followed by HS-SPME exposure at the same temperature under moderate stirring (100 rpm) for 20 min [ 28 ]. Semi-quantification was performed using cyclohexanone as the internal standard and the results were expressed in µg internal standard equivalents/100 g of whole egg, with a detection limit of 0.01 µg/100 g of whole egg.…”
Section: Methodsmentioning
confidence: 99%